AB0312 US7 scoring systems follow-up 48 weeks TNF-A antagonists plus mtx treatment for high disease activity refractory rheumatoid arthritis. (15th June 2017) - Lin, DF; Gu, X; Cao, J; Pan, Y; Gu, J
Abstract : Background: US7 score is the ultrasound scoring system for rheumatic arthritis (RA) with the most clinical evidence so far. Several reports accessed its inter-, intra-observer agreement, its specificity, sensitivity and practical possibility compared to more complex scoring systems such as 72-joints scoring systems, which showed it is an convenient tool for clinical use. Objectives: Our goal is to employ US7 to investigate the ultrasonic changes during biological agents plus MTX Treatment in high disease activity refractory RA patients in Yellow people. Methods: All cases were diagnosed as RA fulfilling 2009 ACR/EULAR classification criteria and evaluated as high disease activity for DAS28>5.1 with MTX+HCQ+SASP or MTX+LEF invalid therapy for more than 3 months before baseline. Biological agents including TNF-a antagonist or IL-6 antagonist plus with MTX 10mg qw were then given and ultrasound was performed by 2 observers blinded to physicial examinations and blood tests at 0, 4, 12, 24, 48w. US examination referred to US7 scores by Backhaus et al. DAS28 were employed to assess disease activity. Results: 1) 26 subjects were enrolled in the program up to now. 22 were given TNF-a antagonists and 4 were given IL-6 antagonists. 17 finished 24 weeks follow-up. 1 withdrew for TB infection at 12 week and 1 withdrew for fungi pneumonia at 8 weeks. Mean age of 17 was 44.3±11.8 years old, female-male ratio was 15:2, and disease duration was 71 months. All were RF and ACPA postIve. 2) DAS28-CRP, DAS28-ESR had prominent decrease from 0 to 24 week (DAS28-CRP: 0w: 4w: 12w: 24w = 6.76, 5.98, 5.09, 4.48, DAS28-ESR: 0w: 4w: 12w: 24w = 6.36, 4.94, 3.99, 3.35, paired Wilcoxon test, all sig<0.05) 3) The same prominent improvement also well reflected by the ultrasonic scores: average sum scores (0w:4w:12w:24w = 22.9:15.6:13:9.3, all sig <0.05 except 4w: 12w, sig=0.126), synovitis grey scale scores (0w:4w:12w:24w = 11.6:9.3:8.1:6.0, all sig <0.05, except 0w:4w, sig=0.068), synovitis Power Doppler scores (0w:4w:12w:24w = 8.5:4.9:3.8:2.7, all sig <0.05, except 4w:12w, 4w:24w, 12w:24w, sig = 0.361, 0.227, 0.235), tenosynovitis grey scale scores (0w:4w:12w:24w = 0.63:0.25:0.25:0.07, all sig <0.05, except 4w:12w, 4w:24w, 12w:24w, sig = 1.0, 0.26, 0.26), tenosynovitis Power Doppler scores (0w:4w:12w:24w = 1.00:0.19:0:0 all sig <0.05, except 4w:12w, 4w:24w, 12w:24w, sig = 0.18, 0.18, 1.0), bone erosion scores (0w:4w:12w:24w = 1.2:1.0:0.94:0.53, all sig <0.05 except 0w:4w, 4w: 12w, 4w:24w, 12w:24w, sig = 0.083, 0.317, 0.102, 0.102). The above data showed the sum scores found biological agents improved thorough the whole course as Das28 did. Synovitis seemed to be eliminiated faster than tenosynovitis and the repair of bone erosion was the latest event compared to decreased synovitis and tenosynovitis. Conclusions: It is recommended US7 used in clinic for US7 scoring system could reflect more exquisitely than DAS28 in more refined aspects including the changes of tendon, joint, bone at different phrases during biological agent treatment for RA. However, more samples should be included in our study to illuminate above conclusion with sufficient evidence. Disclosure of Interest: None declared